The effect of audit systems and internal control on auditor non compliance: the mediating role of audit detection errors - Fitriyansyah Fitriyansyah; Gema Ika Sari; Udin Suadma (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study examines the persistent issue of auditor non-compliance in local government institutions despite the formal implementation of audit systems and internal control mechanisms. Although regulatory frameworks and supervisory structures have been established, practical weaknesses remain evident, particularly in audit detection errors. The purpose of this research is to analyze the effects of system audits and internal control on auditor non-compliance, and to investigate the mediating role of audit detection errors in regional government agencies of Pandeglang Regency. A quantitative explanatory approach was employed using data collected from 96 respondents through structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results indicate that system audits and internal control significantly reduce audit detection errors and auditor non-compliance. Detection errors have a positive and significant effect on auditor non-compliance and partially mediate the relationships between governance mechanisms and compliance behavior. These findings highlight that improving detection capability is crucial for strengthening audit quality and public sector accountability.